2007
DOI: 10.2298/apt0738097t
|View full text |Cite
|
Sign up to set email alerts
|

The extremely high stability of carbofuran pesticide in acidic media

Abstract: Environment friendly iron catalysts were applied in the decomposition reactions of some toxic compounds like phenol, methomyl and corbofuran pesticide. The applied catalytic processes belong to photo-Fenton reactions. Heterogeneous iron catalysts showed significant activity in phenol and methomyl conversion, however, these catalysts were completely inactive in destruction of carbofuran molecule, even in the catalytic reaction promoted with UV light at high temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The degradation observed in the presence of ZnO under irradiation confirmed that the process takes place in a photocatalytic regime. The highest photocatalytic degradation rate of carbofuran in our earlier investigation (Tomašević et al, 2007) was obtained for 2 g L -1 of ZnO. Therefore, 2 g L -1 of photocatalyst was chosen as the concentration in all photocatalytic degradation experiments performed in this study.…”
Section: Effect Of Reaction Time On Photocatalytic Degradation Of Carmentioning
confidence: 93%
“…The degradation observed in the presence of ZnO under irradiation confirmed that the process takes place in a photocatalytic regime. The highest photocatalytic degradation rate of carbofuran in our earlier investigation (Tomašević et al, 2007) was obtained for 2 g L -1 of ZnO. Therefore, 2 g L -1 of photocatalyst was chosen as the concentration in all photocatalytic degradation experiments performed in this study.…”
Section: Effect Of Reaction Time On Photocatalytic Degradation Of Carmentioning
confidence: 93%
“…Table 6. Pseudo-first-order rate constants of methomyl photodegradation in presence of AlFe-PILC and Fe-ZSM-5 catalysts [19] The heterogeneous photo-Fenton reaction in methomyl and carbofuran water solutions (1.0 x 10 -4 M) in a glass batch reactor at constant pH (3.5-4.0), in the presence of AlFe-pillared clay catalyst (PILC) and Fe-ZSM-5 zeolite catalyst (both 5.0 g/L), under halogen lamp light (575.6 nm) was investigated [76,82]. The applied catalysts decomposed methomyl successfully but were inactive for carbofuran degradation.…”
Section: Heterogeneous Photocatalysismentioning
confidence: 99%
“…Carbofuran could not be mineralized by the use of AlFe-PILC and Fe-ZSM-5 zeolite catalysts, even in a high-temperature catalytic reaction. The high chemical stability of the carbofuran molecule may be explained by its electronic structure, but this claim requires further theoretical and experimental investigations [76,82].…”
Section: Heterogeneous Photocatalysismentioning
confidence: 99%
“…The TOC measurement indicate an efficient mineralization of 93 and 94% respectively, for photo-and electro-Fenton processes after 480 min of treatment. Carbofuran could not be mineralized on AlFe-PILC and Fe-ZSM-5 zeolite catalysts in the heterogeneous photo-Fenton reactions at 575.6 nm, even in the catalytic reaction promoted at high temperature (Tomašević et al, 2007a(Tomašević et al, , 2007b.…”
Section: Carbofuranmentioning
confidence: 99%